Sosialisasi Pengenalan Diri Dan Pengembangan Potensi Untuk Meraih Prestasi Di SMK Negeri 2 Panyabungan - Liantha Adam Nasution; Nadia Syahida LBS; Nurhidayah Lubis; Nursatia Ritonga; Risna Hanani Lubis; Elvina Sari Lubis; Muhammar Hanafi (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Self-potential is the ability that each person has that has the possibility to be developed. Knowing oneself is the basic principle of every determination of one's life. The goal is that by recognizing oneself, it will be able to make someone determine what his dreams are. Everyone must have a dream, where the dream is able to bring him to determine his life goals. This socialization activity was carried out at SMK Negeri 2 Panyabungan with three methods, namely preparation, implementation and evaluation. Everyone must be able to recognize, understand, and accept who they are as best as possible. By understanding oneself, a person will be able to achieve success because they will be able to behave more effectively. To know oneself, one must also know one's strengths and weaknesses and never think of comparing oneself with others because everyone has their own privileges.